Energy management study: A proposed case of government building - Tahir, Mohamad Zamhari; Mohd Nawi, Mohd Nasrun; Baharum, Faizal (2014)
Align with the current needs of the sustainable and green technology in Malaysian construction industry, this research is conducted to seek and identify opportunities to better manage energy use including the process of understand when, where, and how energy is used in a building.The purpose of this research is to provide a best practice guideline as a practical tool to assist construction industry in Malaysia to improve the energy efficiency of the office building during the post-production by reviewing the current practice of the building operation and maintenance in order to optimum the usage and reduce the amount of energy input into the building. Therefore, this paper will review the concept of maintenance management, current issue in energy management, and on how the research process will be conducted.There are several process involves and focuses on technical and management techniques such as energy metering, tracing, harvesting, and auditing based on the case study that will be accomplish soon. Accordingly, a case study is appropriate to be selected as a strategic research approach in which involves an empirical investigation of a particular contemporary phenomenon within its real life context using multiple sources of evidence for the data collection process.A Government office building will be selected as an appropriate case study for this research. In the end of this research, it will recommend a strategic approach or model in a specific guideline for enabling energy-efficient operation and maintenance in the office building.